Pengaruh Independensi, Skeptisisme Profesional Auditor, Penerapan Standar Audit, dan Etika Audit Terhadap Kualitas Hasil Audit (Studi pada Auditor BPK RI Perwakilan Provinsi Aceh) - Ningsih, Fatria; Nadirsyah, Nadirsyah (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2017)
Audit Quality is not easy to define because of many diverse factors affecting quality. This study aims to determine the effect of Independence, Auditor Professional Skepticism, Standards Implementation Audit, and Ethics Audit on the Audit Quality. The data used in this study are primary data by spreading the questionnaire to all auditors in BPK RI Representative province office in Aceh. The population in this study are all auditors at BPK-RI representative office in Aceh. The collecting of data and information needed in this research was done by field research. The data used is primary data collected directly from the subject of research by a questionnaire form. The testing of the influences of independent variables toward dependent variables was done by using multiple regressions model. The results of this research shows that both partially and simultaniously, Independence, Auditor Professional Skepticism, Standards Implementation Audit, and Ethics Audit are influential to the Audit Quality in BPK RI Representative province office in Aceh.